Computed Tomography–Guided Microcoil Localization of Pulmonary Nodules: Effects of Multiple Punctures - Tian, Ye; An, Jianli; Zou, Zibo; Dong, Yanchao; Wu, Jingpeng; Chen, Zhuo; Niu, Hongtao (The Thoracic and Cardiovascular Surgeon, 2021)
Background The aim of the study is to analyze the effect of multiple punctures in computed tomography (CT)-guided microcoil localization of pulmonary nodules with other risk factors for common complications.Methods Consecutive patients who underwent CT-guided microcoil localization and subsequent video-assisted thoracoscopic surgery (VATS) between January 2020 and February 2021 were enrolled. Nodules successfully located after only one puncture were defined as the single puncture group, and nodules requiring two or more punctures were defined as the multiple puncture group. Binary logistic regression analysis was performed to assess the relationship between the number of punctures and pneumothorax and intrapulmonary hemorrhage.Results A total of 121 patients were included. There were 98 (68.1%) pulmonary nodules in the single puncture group compared with 46 (31.9%) nodules in the multiple puncture group. The frequencies of pneumothorax and intrapulmonary hemorrhage were higher in the multiple puncture group than in the single puncture group (p = 0.019 and <0.001, respectively). Binary logistic regression demonstrated that independent risk factors for developing pneumothorax included lateral positioning of the patient (p < .001) and prone positioning (p = 0.014), as well as multiple punctures (p = 0.013). Independent risk factors for intrapulmonary hemorrhage included the distance between the distal end of the coil and the surface of the pleura (p = 0.033), multiple punctures (p = 0.003), and passage through the pulmonary vasculature (p < 0.001).Conclusion Multiple punctures resulted in an increased incidence of pneumothorax and intrapulmonary hemorrhage compared with single puncture during CT-guided microcoil localization of pulmonary nodules and were independently associated with both pneumothorax and intrapulmonary hemorrhage.
Keywords: VATS; minimally invasive surgery; complications